Do individually ventilated cage systems generate a problem for genetic mouse model research?. (23rd July 2014) - Logge, W.; Kingham, J.; Karl, T.
<x xml:space="preserve">Abstract</x> Technological developments over recent decades have produced a novel housing system for laboratory mice, so‐called 'individually ventilated cage' (IVC) systems. IVCs present a cage environment which is different to conventional filter‐top cages (FILTER). Nothing is known about the consequences of IVC housing on genetic mouse models, despite studies reporting IVC‐mediated changes to the phenotypes of inbred mouse strains. Thus, in this study, we systematically compared the established behavioural phenotype of a validated mouse model for the schizophrenia risk gene neuregulin 1 (TM Nrg1 HET) kept in FILTER housing with Nrg1 mutant mice raised in IVC systems. We found that particular schizophrenia‐relevant endophenotypes of TM Nrg1 HETs which had been established and widely published using FILTER housing were altered when mice were raised in IVC housing. IVCs diminished the schizophrenia‐relevant prepulse inhibition deficit of Nrg1 mutant males. Furthermore, IVC housing had a sex‐dependent moderate effect on the locomotive phenotype of Nrg1 mice across test paradigms. Behavioural effects of IVC housing were less prominent in female mice. Thus, transferring the breeding colony of mouse mutants from FILTER to IVC systems can shift disease‐relevant behaviours and therefore challenge the face validity of these mice. Researchers facing an upgrade of their mouse breeding or holding facilities to IVC systems must be aware of the potential impact this upgrade might have on their genetic mouse models. Future publications should provide more details on the cage system used to allow appropriate data comparison across research sites.